2022
DOI: 10.1021/acs.orglett.2c01238
|View full text |Cite
|
Sign up to set email alerts
|

Construction of N-Acyliminophosphoranes via Iron(II)-Catalyzed Imidization of Phosphines with N-Acyloxyamides

Abstract: Employing FeCl 2 as a cheap and readily available catalyst, a facile imidization of phosphines with N-acyloxyamides is described, affording synthetically useful N-acyliminophosphoranes with high functional group tolerance. The transformation is easily performed under an air atmosphere at room temperature and could be scaled up to gram scale with a catalyst loading of 1 mol %. The iminophosphoranyl moiety in the product was further utilized as an effective directing group for controllable ortho C(sp 2 )−H bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…59 In addition, their group achieved a facile imidization of phosphines with N-acyloxyamides by using FeCl 2 as the catalyst (Scheme 31c). 60 Lebel et al documented a diastereoselective amination of thioethers with chiral N-mesyloxycarbamate S-14 for the synthesis of chiral sulfilimines (Scheme 32). 61,62 The reaction was performed with Rh 2 [(S)-nttl] 4 previously used for asymmetric Csp 3 -H amination, and its structure has been shown in Scheme 8.…”
Section: N-x Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…59 In addition, their group achieved a facile imidization of phosphines with N-acyloxyamides by using FeCl 2 as the catalyst (Scheme 31c). 60 Lebel et al documented a diastereoselective amination of thioethers with chiral N-mesyloxycarbamate S-14 for the synthesis of chiral sulfilimines (Scheme 32). 61,62 The reaction was performed with Rh 2 [(S)-nttl] 4 previously used for asymmetric Csp 3 -H amination, and its structure has been shown in Scheme 8.…”
Section: N-x Bond Formationmentioning
confidence: 99%
“…59 In addition, their group achieved a facile imidization of phosphines with N -acyloxyamides by using FeCl 2 as the catalyst (Scheme 31c). 60…”
Section: Hydroxylamide-derived Acyl Nitrene Precursorsmentioning
confidence: 99%
“…Bittner and Pomerantz demonstrated that amide could be converted to phosphinimidic amides by treatment with stoichiometric quantities of phosphines and diethyl azodicarboxylate (DEAD) . More recently, the transformation of nitrene has been regarded as a powerful access to this class of compounds. Under photoirradiation, dibenzothiophene N -substituted sulfilimines and dioxazolones were utilized as nitrene precursors by the groups of Morita and Bao, respectively. During the preparation of this manuscript, Xia and co-workers reported an Fe­(II)-catalyzed imidization of phosphines with N- pivaloyloxyamides …”
mentioning
confidence: 99%
“…During the preparation of this manuscript, Xia and co-workers reported an Fe(II)-catalyzed imidization of phosphines with N-pivaloyloxyamides. 12 Taking advantage of the rapidly developed photochemistry, 13 phosphoranyl radical-mediated fragmentation provided an attractive way to access carbon-centered radicals via the deoxygenation of carboxylic acids and alcohols (Scheme 1B). 14,15 However, the activation of N−O bond for the generation of nitrogen-centered radicals 16 is less developed.…”
mentioning
confidence: 99%
“…On the basis of our previous mechanistic investigations on the C–H activation reactions, we found N -acyloxyamides could serve as mild and stable N -acyl nitrene precursors . Following our interests in the field, in the current report we applied the N -acyloxyamides for N -acyl nitrene transfer of sulfoxides using iron­(II) salt as the catalyst, opening a facile access to various N -acyl sulfoximines [Scheme b, (3)].…”
mentioning
confidence: 99%